PATHOPHYSIOLOGY OF BRONCHIAL ASTHMA - Razhabova Zebiniso Safarovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Bronchial asthma is a chronic inflammatory disease of the airways characterized  by  bronchoconstriction,  airway  hyperresponsiveness,  and  excessive mucus production. It results in episodic airflow obstruction and respiratory distress. This article explores the pathophysiological mechanisms underlying bronchial asthma, highlighting the role of immune responses, inflammation, and airway remodeling in disease progression.